Outdoor Learning in Early Childhood Education : A Narrative Review - Lindfors Eila; Rönkkö Marja-Leena; Kiviranta Leena; Yliverronen Virpi; Tanhuanpää Saija; Grönman Satu (Universitetsbiblioteket OsloMet, 2022)
Outdoor learning environments can be beneficial in enhancing children’s engagement and motivation in different activities. Outdoor learning environments have the potential to enable transforming and meaningful experiences with imagination and play as well as to evoke ideas for craft, design, and technology education. This study aims to describe outdoor learning implementation in early childhood education based on previous studies. For this, the following research question is addressed: What are the typical opportunities and challenges in implementing outdoor learning in early childhood education? The answer is discussed in accordance with craft, design, and technology education in early childhood. The methodological approach of this study is a narrative review. The data includes 10 peer-reviewed journal articles and book chapters, which were categorized into six categories: All-around development of children, Well-being, Multimodal hands-on learning possibilities, Nature as a resource, Teachers as mediators, and Organization. From the basis of the results, it seems obvious that carrying out CDT projects as outdoor learning would benefit children’s all-around development and well-being as well as enhance their multimodal hands-on learning opportunities. The results can be taken as a basis for researchers to plan an empirical study in outdoor contexts. They can also serve teachers as they plan a technology learning project in an outdoor environment with their younger students and teacher training in outdoor environments.